Where do parties talk about what? Party issue salience across communication channels - Christoph Ivanusch (West European Politics, 2025)
Political parties address the public through multiple communication channels simultaneously, but this is not reflected in contemporary research. It is largely unclear how party competition plays out across different communication channels and whether issue salience strategies depend on the channel used. In order to answer this question, this article trains a state-of-the-art language model (BERT) on labelled manifestos and applies it for cross-domain topic classification of press releases, parliamentary speeches and tweets from parties and individual party members in Austria, Germany and Switzerland. The results show that certain channel characteristics influence parties' issue salience. The extent to which a party addresses its issue preferences (ideal agenda) is moderated by the degree of centralised communication (party vs. individuals) and the presence or absence of a pre-given agenda, whereas a channel's primary audience (direct vs. mediated channel) plays a much smaller role than expected. These findings illustrate the complexity of party competition in contemporary multi-channel and hybrid media environments.
Keywords: 320; Party competition; issue salience; communication channels; cross-domain topic classification